2017
DOI: 10.1080/15384047.2017.1394553
|View full text |Cite|
|
Sign up to set email alerts
|

HIF2Agermline–mutation-induced polycythemia in a patient with VHL-associated renal-cell carcinoma

Abstract: In this study, we report here a rare case of polycythemia and cRCC in the same patient, which may be helpful in understanding clinical features and molecular mechanisms underlying VHL–mutation-associated cRCC and polycythemia induced by germline mutation of HIF2A. Firstly, we identified a rare but well studied germline mutation resulting in polycythemia in HIF2A (c.1609G>A, p.Gly537Trp) in the blood of the patient and his daughter. Meanwhile, we identified an inactivating VHL mutation (c.391A>T, p.N131Y), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The first EPAS1 variants found in patients with FE in year 2008 were p.Met535Val, p.Gly537Arg, and p.Gly537Trp, all located in exon 12 . Subsequent studies revealed additional erythrocytosis‐associated EPAS1 variants on amino acid positions 525, 532, 533, 534, 535, 537, 539, 540, and 544 in exon 12; position 374 in exon 9 ; position 822 in exon 16; and deletion on 17 aa residue in exon 2 . According to UniProt database, six variants in exon 12 (p.Pro534Leu, p.Met535Thr, p.Met535Val, p.Gly537Arg, p.Gly537Trp, p.Phe540Leu) have been confirmed as a cause for ECYT4 and are together with variant p.Asp539Glu listed in the LOVD database .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first EPAS1 variants found in patients with FE in year 2008 were p.Met535Val, p.Gly537Arg, and p.Gly537Trp, all located in exon 12 . Subsequent studies revealed additional erythrocytosis‐associated EPAS1 variants on amino acid positions 525, 532, 533, 534, 535, 537, 539, 540, and 544 in exon 12; position 374 in exon 9 ; position 822 in exon 16; and deletion on 17 aa residue in exon 2 . According to UniProt database, six variants in exon 12 (p.Pro534Leu, p.Met535Thr, p.Met535Val, p.Gly537Arg, p.Gly537Trp, p.Phe540Leu) have been confirmed as a cause for ECYT4 and are together with variant p.Asp539Glu listed in the LOVD database .…”
Section: Resultsmentioning
confidence: 99%
“…4,6,23,24,[26][27][28]62 Therefore, significantly more clinical research studies in association with erythrocytosis were performed on EPAS1 gene. All indicated variants in EPAS1 and HIF3A genes were identified in patients with FE or idiopathic erythrocytosis, 9,49,50,[52][53][54][55][56][57][58][59][60][61]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, an infant carrier was diagnosed with leukoencephalopathy without PCC/PGL ( 33 ); a 19-year-old female carrier was diagnosed with hereditary oncolytic renal cancer ( 31 ) and an 11-year-old boy was diagnosed with polycythemia and abdominal PGL ( 32 ). In 2017, our team reported a case with a HIF2A somatic mutation-induced polycythemia and PCC and a case of HIF2A germline-mutation-induced polycythemia in a patient with VHL-associated renal cell carcinoma ( 17 , 34 ). It is likely for this reason that the pseudohypoxia-related PCC/PGL is fundamentally a metabolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…A gain-of-function germline mutation in HIF-2A alone is not sufficient for tumorigenesis presumably that simultaneous lossof-function in some tumor suppressors is needed. In fact, we recently reported that germline mutations in HIF-2A (c.1609G>A, p.Gly537Arg) are responsible for polycythemia formation and additional somatic VHL mutations are needed for the development of clear-cell RCC (66). Similarly, a germline mutation in HIF-2A exon 9 (c.1121T>A, p.F374Y) leads to polycythemia and predisposes the patients for PPGLs development (67).…”
Section: Hif-a Mutationsmentioning
confidence: 99%